Environmental Life-Cycle Assessment (LCA) of Wireless RF Systems: A Comparative Sustainability Analysis and a Microwave Engineers' Guide to LCA - Mahmoud Wagih; Andrew Bainbridge; Bashayer Alsulami; Jeff Kettle (IEEE Journal of Microwaves)
Information Communication and Technology (ICT) accounts for an increasing share of global Green House Gas (GHG) emissions. Wireless circuits and systems are indispensable in across all ICT sectors, from cellular networks through satellite communications, to the Internet of Things (IoT). While Life Cycle Assessment (LCA) is an industry-standard methodology for assessing the environmental impact of systems, there has been no comprehensive LCA study focusing on RF systems. We present the first comparative LCA specific to RF and microwave applications, and a design-for-sustainability guide covering mainstream RF applications. With Integrated Circuits (ICs) having the largest environmental impact, the trends in RFICs and MMICs are summarized and evaluated from an environmental perspective. Moving to mmWave frequencies, beyond 20 GHz, results in a shift to over 50% smaller node size above 28 GHz, but with minimal reduction in the core chip area, which inevitably increases the environmental footprint of 5G/6G mmWave systems. We then review active and passive microwave circuits focusing on phased array elements and filters, both distributed and lumped. A bespoke model for RF PCBs is also presented to model the surface finish and transmission line or antenna area accurately. Our LCA indicates that design choices such as the CMOS process, PCB material and surface finish, can have a large environmental impact at the manufacturing stage. We highlight the importance of low-loss components, comparing microstrip and LC filters, where a higher end-to-end RF system efficiency directly translates to a lower global warming potential (GWP), reducing Scope 2 GHG emissions.